Reproductive Isolation: Evidence that Ascobolus stercorarius and Ascobolus furfuraceus are two species, not one - G. N. Bistis (Fungal Genetics Reports, 2004)
Strains obtained from the germination of 30-40 year old ascospores from seven stocks of the heterothallicAscobolus stercorarius - furfuraceous complex were mated in all combinations. All st X st and fu X fu pairings were fertile (ascospores) whereas all st X fu pairings were sterile (no ascospores). Based on this reproductive isolation between st and fu strains I conclude that the complex consists of two species. The block that segregated the two species is probably some stage in the establishment of the dikaryotic phase in ascogenous hyphae. One hypothesis is that this block is at the stage of nuclear recognition.